Олена Федорівна Лагодовська — дослідниця доби енеоліту–бронзи - Тарасенко, І.Г. (Археологія, 2017)
Статтю присвячено дослідниці доби енеоліту–бронзи Олені Федоровні Лагодовській. На основі архівних матеріал розкривається її життєвий і науковий шлях. The article describes the life and scientific route of Olena Fedorivna Lahodovska, a researcher of the Chalcolithic and the Bronze Age. Biographical articles about her are few and very brief. Due to the archival materials available, primarily letters, the author managed to wider reveal this scholar’s activities, and even to find out her scientific dreams. O.F. Lahodovska’s academic development took place in collaboration with the famous archaeologists, such as S.S. Hamchenko, P.P. Yefymenko, M.F. Boltenko, as well as with the research centres, such as the Volyn Scientific and Research Museum, DAIMK, Odesa Historical and Archaeological Museum. O.F. Lahodovska is more commonly known as the researcher of Mykhaylivske settlement, the first settlement of Yamna culture. In addition, post-graduate work by Olena Fedorivna was devoted to Globular Amphora culture. She also studied Usatove culture and related issues ofthe Late Trypillia culture and shewasinterested inMiddle Dnipro and Komariv cultures. Discovered in the Scientific Archives in the IA NASU unpublished articles convince that, unfortunately, O.F. Lahodovska had not fully realized herself. В статье рассмотрен жизненный и научный путь исследователя энеолита-бронзы Елены Федоровны Лагодовской. Биографические статьи, посвященные ей очень лаконичны и малочисленны. Благодаря полученному архивному материалу, в первую очередь письмам, удалось шире раскрыть деятельность этого ученого и даже узнать ее научные мечты. Научное становление Е.Ф. Лагодовской происходило в сотрудничестве с такими известными археологами, как С.С. Гамченко, П.П. Ефименко, М.Ф. Болтенко, кроме того оно связано с такими научными центрами как Волынский научно-исследовательский музей, ВУАК, ГАИМК, Одесский историко-археологический музей. Е.Ф. Лагодовская больше известна как исследователь Михайловского поселения, первого поселения ямной культуры. Но кроме этого, аспирантская работа Елены Федоровны была посвящена культуре шаровидных амфор; также она изучала усатовскую культуру и связанные с ней вопросы позднего Триполья, интересовалась среднеднепровской и комаровской культурами. Обнаруженные в НА ИА НАНУ неизданные статьи и готовая к печати книжка, убеждают в том, что Е.Ф. Лагодовской, к сожалению, так и не удалось реализовать себя полностью.